Religious-philosophic dimension of business management consept in the context of oriental discourse - Garnyk, Liudmyla Petrivna; Mokh, J. (Національний університет "Одеська юридична академія", 2018)
In the article are observed philosophic-anthropological and ethical-humanistic aspects of company management nature threw prism of evolution of "Imaginer" theory that gives instruments for theoretical, applied and comparative researches in domain of social sciences. Terms "oriental discourse" and "orientalism" were specified, there were instantiated their nature, essence, origins and formation from viewpoint of subject area of philosophic anthropology. Were analyzed ideas and methodological findings of representatives of "Eranos" School (M. Eliade, A. Corbin, G. Durand, J. Evola, M. Maffesoli) – an philosophic community founded by O. Frobe. On base of analysis of "Imaginer" model of G. Durand it was proposed to enrich philosophic research by applied methodic, borrowed from sociology, psychology and other social sciences.

У статті розглядаються філософсько-антропологічні та етико-гуманістичні аспекти природи управління компанією через призму еволюції метатеорії "Імаджинер", яка надає інструментарій для теоретичних, прикладних і компаративних досліджень у царині суспільних наук. Уточнено поняття "орієнтальнй дискурс" та "орієнталізм", розкрито їх природу, сутність, витоки й формування з огляду на предметне поле філософської антропології. Проаналізовано ідеї та методологічні знахідки представників школи "Еранос" (М. Еліаде, А. Корбен, Ж. Дюран, Ю. Евола, М. Маффесолі) – філософського товариства, заснованого О. Фрьобе. На основі аналізу моделі "Імаджинер" Ж. Дюрана запропоновано вводити до філософського дослідження прикладні методики, запозичені в соціології, психології та інших суспільних наук.
Релігійно-філософський вимір концепту управління компанією в контексті орієнтального дискурсу
Keywords: worldview; traect; symbolic capital; Islam; oriental discourse; світогляд; школа "Еранос"; траект; символічний капітал; Іслам; орієнтальний дискурс